Evaluation of the osmoprotective and bioprotective effect of trehalose 3% - Victor Sendra; Alejandro Berra; Flavia Michelini; Maria Ximena Guerbi; Giselle Rodriguez; Melina Sol del Papa; María Silvia Passerini (The Pan-American Journal of Ophthalmology, 2023)
Purpose: The purpose of this study was to study the osmoprotective and bioprotective effect of trehalose 3% + carboxymethylcellulose (CMC) 0.5% during desiccation conditions. Materials and Methods: Normal human conjunctival epithelial cells (IOBA) were exposed to (1) culture media (control); (2) CMC 0.5% + glycerin 0. 9% + polyethylene glycol 400 0.25% (vehicle); and (3) vehicle + trehalose 3% (trehalose). Cells were treated for 1 h and then exposed to desiccating conditions. Metabolic activity was evaluated by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay and cell viability by trypan blue. Trehalose water retention capability was assessed by a gravimetric analysis. Results: Metabolic activity was maintained during the first 30 min under desiccating conditions with no differences found between groups. After 45 min, metabolic activity decreased both in the control group and the vehicle group, while the trehalose group maintained activity values. Cell viability of the trehalose group was maintained throughout time and was statistically superior to those of the control and the vehicle groups at all evaluated times (P < 0.01). The retention time 20-RT20 - (20% of water retention) was reached at 8 min in the control group, 10 min in the vehicle group, and 15 min in the trehalose group. Conclusions: The addition of 3% trehalose prolonged cell viability and extended water retention time in high-dryness environmental conditions.